Transformasi Paradigma Ensefalopati Hepatikum: Integrasi Gut–Liver–Brain Axis, Neuroinflamasi, dan Biomarker Modern - I Putu Arya Giri Prebawa (Jurnal Ners, 2026)
Hepatic encephalopathy (HE) is increasingly recognized as a complex neuropsychiatric disorder driven by multidimensional interactions within the gut–liver–brain axis rather than ammonia toxicity alone. Recent evidence demonstrates that the synergy between hyperammonemia, systemic inflammation, microbiota dysbiosis, and metabolite dysregulation—particularly bile acids—triggers microglial activation, astrocytic dysfunction, and blood–brain barrier disruption. Sarcopenia and myosteatosis further impair ammonia detoxification and reduce neuroprotective signaling. Emerging biomarkers, including neurofilament light chain (NfL), YKL-40, bile-acid panels, and functional neuroimaging (rs-fMRI, DTI), provide improved sensitivity for early detection of subclinical impairment. Therapeutic strategies now extend beyond ammonia reduction to microbiota modulation (rifaximin, FMT), next-generation ammonia scavengers, and muscle-targeted interventions. Integration of metabolomic profiles with artificial intelligence supports the development of precision medicine approaches, enabling accurate risk stratification and personalized therapeutic planning. This article summarizes the evolving pathophysiological paradigm, diagnostic advances, and future therapeutic innovations in HE.